A standard computable general equilibrium (CGE) model in GAMS - Lofgren, Hans; Harris, Rebecca Lee; Robinson, Sherman (International Food Policy Research Institute, 2002)
Over the past decade, the increasing power and reliability of microcomputers and the development of sophisticated software designed specifically for use with them has led to significant changes in the way quantitative food policy analysis is conducted. These changes cover most aspects of the analysis, ranging from the collections and analysis of socioeconomic data to the conduct of model-based policy simulations... As with any new technology, however, substantial costs in time and money are involved in learning the most efficient ways of using this new technology and then transmitting these lessons to others. This series, Microcomputers in Policy Research, represents IFPRI's ongoing collective experience in adapting microcomputer technology for use in food policy analysis in developing countries....The series is designed to provide hands-on methods for quantities food policy analysis.... The purpose of the fifth volume in the series....is to contribute to and facilitate the use of this class of models in developing countries. The model is written for application at the country level; however, only minimal changes are needed before it can be applied to a region within a country (such as a village) or to a farm household involved in production and consumption activities. The model incorporates features developed over recent years through IFPRI's research projects. These features—of particular importance in developing countries—include household consumption of nonmarketed ("home") commodities, explicit treatment of transaction costs for commodities that enter the market sphere, and a separation be-tween production activities and commodities that permits any activity to produce multiple commodities and any commodity to be produced by multiple activities. The manual discusses the implementation of the model in GAMS (the General Algebraic Modeling System) and is accompanied by a CD-ROM that includes the GAMS files for the model, sample databases, simulations, solution reports, and a social accounting matrix (SAM)." -- from Editors' Introduction